Mitigation of letrozole induced polycystic ovarian syndrome associated inflammatory response and endocrinal dysfunction by Vitex negundo seeds - Tarun Kumar Kar; Sananda Sil; Angshita Ghosh; Ananya Barman; Sandip Chattopadhyay (BMC, 2024)
Abstract Background Polycystic ovary syndrome (PCOS) is a complex endocrine disorder in women that necessitates effective and safe treatment alternatives. This study aimed to evaluate the therapeutic efficacy of Vitex negundo seed in a letrozole-induced PCOS rat model. Results Findings of the present study demonstrated that administration of hydro-ethanolic extract of Vitex negundo (VNE) effectively restored endocrino-metabolic imbalances associated with PCOS, along with correction of antioxidant enzymes level, proinflammatory cytokines, and apoptotic bio-markers. LC-MS analysis confirmed the presence of cinnamic acid, plumbagin and nigundin B as the prominent phytochemicals in VNE. The observed beneficial effects could be attributed to the active compounds in Vitex negundo extract, which exhibited hypoglycemic, hypolipidemic, and catabolic effects on body weight. Additionally, the extract contributed to hormonal balance regulation by modulating the steroidogenic enzymes, specifically by tuning gonadotropins level and correcting the LH:FSH ratio, through the modulation of ERα signalling and downregulation of NR3C4 expression. The antioxidant properties of phytochemicals in Vitex negundo seed were apparent through the correction of SOD and catalase activity. While it's anti-inflammatory and antiapoptotic action were associated with the regulation of mRNA expression of TNF-α, IL-6, BAX, Bcl2. Molecular docking study further indicated the molecular interaction of above mentioned active phytocompounds of VNE with ERα, NR3C4 and with TNFα that plays a critical mechanistic gateway to the regulation of hormone signalling as well as synchronizing the inflammation cascade. Furthermore, the histomorphological improvement of the ovaries supported the ameliorative action of Vitex negundo extract in the letrozole-induced PCOS model. Conclusions This study indicates the potential of Vitex negundo seed as a multifaceted therapeutic option for PCOS. VNE offers a holistic strategy for PCOS with antiandrogenic, anti-inflammatory, and antioxidant properties, driven by its major compounds like cinnamic acid, plumbagine, and nigundin B.